Fiscal effects of migration as a factor increasing disparities in local and regional development – an example of the Opole Voivodeship in Poland - Jończy, Romuald; Rokita-Poskart, Diana (Economic and Environmental Studies, 2020)
In this paper it is attempted, based on the results of empirical studies, to assess the fiscal effects of migration in a peripheral region in Poland. The results presented in the paper show the negative impact of emigration on the budgets of local governments. Migration flows and the lower revenues for local governments may lead to a widening of development disparities between growth centers and remote areas featured with migration outflow.